Recent Achievements in Medicinal and Supramolecular Chemistry of Betulinic Acid and Its Derivatives ‡ - Bildziukevich, Uladzimir; Özdemir, Zülal; Wimmer, Zdeněk (Molecules (Basel, Switzerland), 2019)
The subject of this review article refers to the recent achievements in the investigation of pharmacological activity and supramolecular characteristics of betulinic acid and its diverse derivatives, with special focus on their cytotoxic effect, antitumor activity, and antiviral effect, and mostly covers a period 2015-2018. Literature sources published earlier are referred to in required coherences or from historical points of view. Relationships between pharmacological activity and supramolecular characteristics are included if such investigation has been done in the original literature sources. A wide practical applicability of betulinic acid and its derivatives demonstrated in the literature sources is also included in this review article. Several literature sources also focused on in silico calculation of physicochemical and ADME parameters of the developed compounds, and on a comparison between the experimental and calculated data.
Keywords: fytonutrienty; Pentacyclic Triterpenes; supramolecular self-assembly; kyselina betulinová; cytotoxicity; structural modification; antitumor activity; Structure-Activity Relationship; lidé; chemické jevy; Betulinic Acid; physicochemical parameters; pentacyklické triterpeny; Chemical Phenomena; triterpeny; antiviral activity; betulinic acid; vztahy mezi strukturou a aktivitou; Triterpenes; Phytochemicals; ADME parameters; Humans